Force Sensitive Resistor Feedback with Assistive Walker Device - Hazem Ali Jasim; Hassanain Ali Lafta (Genius Journals, 2022)
Fear of falling might cause older people to limit their involvement in activities. When the user begins to utilize the walker, a force from the walker's handle is applied. Force feedback is a significant component for many of these walkers, providing the user and physician with valuable information that leads to an improved quality of life for the subject. A force-sensitive resistor (FSR) was used for this function in the recommended system. Depending on how much pressure is put on the sensing area, this FSR's resistance changes. FSR was attached to a resistor, and interfaced with the Atmega328p microcontroller to connect it to a microcontroller. The quantifiable data generated by the force sensor enables to determine pressure ranges (light touch, light squeeze, medium squeeze, strong squeeze). These readings were illustrated in the form of a graph for two groups, the first, Group A, which includes six young adults; and the second, Group B, which includes six elderly participants. The FSR was calibrated to acquire precise force values applied to the exposed surface. The final relationships established between the applied force and the voltage, resistance, and conductance values of FSR sensor
Keywords: Embedded Microcontroller; FSR; Multisensors; Smart Walker